PERAN WKS. KESISWAAN DALAM MENGEMBANGKAN EKSTRAKURIKULER DI SMK DARUSSALAM BLOKAGUNG TAHUN PEMBELAJARAN 2019/2020 - Amirotun Nahdliyah; Fathul Amin (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Abstract This study aims to determine and describe the role of student management in developing student talent in extracurricular activities and to find out the supporting factors and inhibitors of extracurricular activities in SMK Darussalam 2019/2020 academic year. This type of research is a type of field research or qualitative research. The method used is observation, interview and documentation. Analysis of the data used is descriptive qualitative, while the subject of research is the Student WKS. and extra responsibility. Based on the results of the study it can be concluded that student management has a positive role in developing student talent, namely: controlling and taking responsibility for extra walking, extracurricular activities held can increase student talent in the arts. This is proven by the various achievements that students have achieved. Supporting factors: a support from the school is needed to support the smooth development of extracurricular activities in Darussalm Middle School. Schools in Darussalam strongly support extracurricular activities both in the provision of materials and facilities as well as licensing in carrying out extracurricular activities. Inhibiting factors: The time for extracurricular activities in Darussalam is carried out by taking active hours of learning. does not interfere with learning activities in Darussalam.